Perbaikan Kualitas Pupuk Kandang Sapi dan Aplikasinya pada Tanaman Jagung Manis (Zea mays saccharata Sturt) - Ariyanto, Shodiq Eko (Universitas Muria Kudus, 2011)
Effort renders for sustainable agriculture to back up agricultural product that most free from chemical material recidu gets to be done by organic farming. This research intent to get bioactifator that can increase organic fertiliser quality of cow filth via ferment, seeing is purpose impact manures to usufruct that ferment to soiled quality, and gets manure dose usufruct ferment who can increase organic ala sweet corn productivity. Executed research at Bageng Village, Gembong District, Pati Regency and Agriculture Faculty Production Laboratory Muria Kudus University on month of June until with September 2011. The Research factorial utilizes Random Completly Block (RCBD) one that consisting of two factors. First factor is type manure ferment result crib comprise of two factors (2x3) + 1 control (D0), first type factor bioactifator (J ) comprise of: J1 = EM 4; J2 = local microorganism (MOL), and second factor dosed crib manure usufructs comprise of ferment: D1 = 5 tons -1 ha; D2 = 10 tons -1 ha; D3 = 15 tons -1 ha. Total treatments seven treatment and each at three replications. Watch: (1 ) quality manure to usufruct cow filth ferments; (2 ) soiled qualities: pH, C-organic, capacity exchange cations, pospor content, potassium content; (3 ) growth and plant developings: plant weight is dry, cob weight per plant, and cob weight per hectare. Treatment bioactifator observational result on processes cow filth ferment Efective Microorganisme-4 (EM-4) and also local microorganism (MOL) having for increase manure quality. Type manures and organic fertiliser dose usufruct den manure ferment on sweet corn plant, having for to soiled quality step-up covers: pH is soil, C organic, KTK, P total soil, and availibility of potassium; doses 15 ton -1 best ha for bioactifator second. Despitefully gets to increase plant dry weight, cob weight per plant, and cob weight per sweet corn plant hectare, doses 10 ton -1 hectare is the best; ferments yielding organic fertiliser EM 4 point out better than MOL result.